Genre aspect of a language personality of an interpreter - Ulanova, Ekaterina Эдуардовна; Katermina, Veronika Викторовна (Жанры речи)
The article deals with the problem of genre in translation studies. The hypothesis of the study is the idea of the genre shifts emerging at the moment of interpreting within the genre of a TV interview. The authors discuss the ways of interpreting the genre. In accordance with the functional-linguistic approach to the analysis of speech genre, the authors consider the ways in which the linguistic personality of the interpreter verbally regulates the translation of the genre. The authors structurally describe the material, methods and results of the study. The aim of the study includes the linguistic analysis of genre shifts, ways of overcoming them and description of speech means of realization of a genre by the linguistic personality of a conference interpreter. The authors substantiate the logic of choosing the genre type, list the characteristic features of the genre of the television interview of portrait type. The researchers use the method of comparative analysis of the genre’ “projection” and linguocognitive analysis of the stylistic parameters of the scripts of interpretation and consider the ways of genre preservation in interpreting realized by conference interpreters. The linguistic analysis hereby considers translation solutions (transformations) at the lexico-semantic and grammatical levels; ways of expressing the genre through the use of background knowledge and extra-linguistic context; ways of translating genre conventions (the key condition of a genre). They analyse translation mistakes as a way of a genre expression. The distinctive features of the English- and Russian-language genre of the TV interview are listed on the grounds of the performed simultaneous translations. The results of the study demonstrate the future prospects of genre research, including the analysis of the of conscious and unconscious genre preservation/ breakage in interpreting.